Leprosy in pre‐Norman Suffolk, UK: biomolecular and geochemical analysis of the woman from Hoxne. Issue 11 (November 2017) - Inskip, Sarah; Taylor, Michael G.; Anderson, Sue; Stewart, Graham
Abstract : Purpose. : A woman's skull, exhibiting features of lepromatous leprosy (LL), was recovered from a garden in Hoxne, Suffolk. The absence of post crania and lack of formal excavation meant that diagnosis and dating was uncertain. The aim of this research was to confirm the diagnosis using biomolecular means and second, to place it in context with other British leprosy cases using SNP genotyping and radiocarbon dating. Methodology. : Bone from the skull was analysed by ancient DNA (aDNA) methods and subjected to radiocarbon dating. As a result, stable carbon and nitrogen isotope values were produced, both useful for assessing aspects of the woman's diet. Results/Key findings. : aDNA confirmed the presence of mycobacterium leprae and genotyping demonstrated an ancestral variant of subtype 3I, the same lineage recently identified in living squirrels in the south of England. Radiocarbon dating revealed the woman lived approximately between 885‐1015 AD, providing evidence for endurance of this subtype in East Anglia, having been previously identified as early as the fifth‐sixth century (Great Chesterford) and as late as the thirteenth century (Ipswich). Conclusions. : The confirmation of a new pre‐Norman leprosy case in East Anglia is of interest as this is where a high proportion of cases are located. Possible factors for this may include preservation and excavation biases, population density, but also connection and trade, possibly of fur, with the continent. Future research on other British LL cases should focus on exploring these aspects to advance understanding of the disease's history, here and on the continent.